A novel meta-heuristic algorithm based optimized load frequency controller - Majahar Hussain Mahammad; Chekka Ravi Kumar (Institute of Advanced Engineering and Science, 2022)
This work proposes a 2-degree-of-freedom proportional-integral-double-derivative (2-DOF PIDD) controller to improve frequency profiles of an IEEE 39 bus 10 generator 3 area New England interconnected power system during step load perturbations. To increase the system’s dynamic response, parallel derivative components are used in the secondary controller mechanism, and comparisons are made with proportional, integral and derivative (PID) and 2-DOF PID controllers to illustrate the advantage of the proposed controller scheme. The ideal gain values of the PID, 2-DOF PID, and 2-DOF PIDD controllers are achieved using a novel evolutionary algorithm called the intelligent water drops (IWD) algorithm, which is used for the first time for the load frequency control problem for a 3-area power system. The results proved that the proposed controller is superior to the existing controllers. Simulations are done in the MATLAB-Simulink® environment.